استخدام مواقع التواصل الاجتماعي – فيسبوك – كمصدر للمعلومات الصحية لدى طلبة المعهد الوطني للتكوين العالي شبه طبي -المسيلة- - عويرة نور الدين, شريفي صبرينة (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2021)
لقد اصبحت مواقع التواصل الاجتماعي اليوم من اهم منتجات تكنولوجيا الاتصال وأكثرها شعبية وخاصة الفيسبوك الذي امتد استخدامه الى تحقيق اهداف مختلفة تعود على الفرد والمجتمع كالصحة والتعليم وباعتبارهما مطلب انساني لذلك فعلى الرغم من تعدد مصادر المعلومات الصحية وخاصة لدى طلبة التخصص فان الفيسبوك اكتسب أهمية بالغة ضمن هذه المصادر حيث انه يشهد حركية دائمة من التطور والانتشار من خلال ما يقدمه من معلومات يستعين بها طلبة المعهد الوطني للتكوين العالي الشبه طبي بالمسيلة ضمن مسارهم التكويني والاكاديمي ثم المهني لهذا جاءت دراستنا هذه للكشف عن مدى استخدام مواقع التواصل الاجتماعي الفيسبوك كمصدر للمعلومات الصحية والاشباعات المحققة منها من خلال دراسة عينة من طلبة المعهد الوطني للتكوين العالي الشبه طبي بالمسيلة، ومن اجل اختيار فرضيات الدراسة تم الاعتماد على المنهج الوصفي التحليلي وتطبيق أداة الاستبيان على عينة قصدية من طلبة التخصصات النهائية للمعهد (ممرضون ومخبريون للصحة العمومية السنة الثالثة وقابلات للصحة العمومية السنة الخامسة) وقد احتوى الاستبيان على عدة محاور: - محور متعلق بالبيانات الشخصية للمبحوثين - وثلاث محاور مرتبطة باختبار الفرضيات حيث خصص المحور الأول لعادات وانماط استخدام مواقع التواصل الاجتماعي الفيسبوك بينما خصص المحور الثاني لطبيعة المحتوى الصحي والمعرفي الذي يبحث عنه الطالب من خلال الفيسبوك ودوافع استخدامه، اما المحور الثالث فخصص للاشباعات المحققة من خلال استخدام موقع الفيسبوك كمصدر للمعلومات الصحية. -وبعد المعالجة الكمية والكيفية توصلنا الى مجموعة من النتائج كصورة تعكس الدراسة بشقيها النظري والتطبيقي Today, social media has become one of the most important and most popular telecommunication means, especially Facebook, which has extended its use to achieving various humanitarian purposes that affect the individual and society as well , such as health and education, Therefore, despite the multiplicity of health information sources, especially among students of specialization, Facebook has gained great importance within these Sources as it is witnessing a constant movement of development and spread through the information it provides that students of the National Institute for Higher Paramedical Training can use in question within their formative, academic and then professional career. That's why our study came to reveal the extent to which the use of Facebook as a source of health information and the satisfaction obtained from such website. we conducted a study of a sample of the students of the National Institute of Higher Paramedical Training in M'sila. In order to choose the hypotheses of the study, we followed the descriptive and analytical approach and the questionnaire tool was applied to a sample of the institute graduates (public health and lab nurses in the third year and public health midwives in the fifth year) and the questionnaire contained several sections: - A topic related to the informant’s personal data. - And three sections are related to hypothesis testing, where the first one is devoted to the habits and patterns of use of social media -Facebook-. The second is devoted to the nature of health content and health information that the student searches for through Facebook and the motives for its use, while the third is devoted to the satisfaction achieved through the use of Facebook as a source of information related to their domain. After the quantitative and qualitative treatment, we came to a set of results as an image that reflects both theoretical framework and field study
Keywords: use - social media - Facebook - health information مواقع التواصل الاجتماعي – الفيسبوك – المعلومات الصحية